Efeito do aduto de Morita-Baylis-Hillman 2-(3-hidroxi-2-oxoindolin-3-il)acrilonitrila (ISACN) na inflamação aguda experimental: abordagens in vivo e in vitro - Silva, Juliane Santos de França da (2021)
Inflammation is a physiological response of the body, essentially beneficial. However, when exacerbated, inflammation is involved in the pathogenesis of numerous diseases, and drugs with anti-inflammatory properties are routinely used in the clinic. Currently, anti-inflammatory drugs available on the market have numerous adverse effects. Thus, it is necessary to search for new therapeutic strategies with safer anti-inflammatory drugs. 2- (3-Hydroxy-2-oxoindolin-3-yl) acrylonitrile (ISACN) is a Morita-Baylis-Hillman’s adduct derived from isatin that has anti-tumor and antibacterial action in addition to low acute toxicity, low risk of genotoxicity and good theoretical bioavailability by the oral route. Therefore, the aim of this work was to investigate the anti-inflammatory effect of ISACN and to determine its mechanism of action. For that, we used zimosan-induced peritonitis, acute lung injury (ALI) induced by bacterial lipopolysaccharide (LPS) and the culture of murine peritoneal macrophages stimulated with zimosan or LPS as experimental models. Initially, female Swiss mice were treated intraperitoneally (i.p.) with different doses of ISACN (1.5 mg/kg; 6mg/kg and 24 mg/kg) and subjected to experimental peritonitis through the challenge (ip) with zimosan (2mg/mL). The treatment with ISACN reduced the migration of neutrophils and the production of cytokines IL-1β, IL-6 and TNF-α. Male Balb/c mice were treated with 24 mg/kg of ISACN (i.p.) and subjected to experimental ALI through intranasal challenge (i.n) with LPS (2.5 mg/kg). The treatment with ISACN reduced the migration of neutrophils, the formation of pulmonary edema and the production of cytokines IL-1β, IL-6 and TNF-α, and reversed the histopathological changes characteristic of ALI. For in vitro experiments, murine peritoneal macrophages were cultured in the presence of different concentrations of ISACN (20μM, 10μM, 5μM) and stimulated with zimosan (0.2 mg/mL) or with LPS (1 μg / mL). The concentration of 20 μM was shown to be cytotoxic while the concentrations of 10 μM and 5 μM did not promote considerable changes in the viability of macrophages. During the culture of zimosan-stimulated murine peritoneal macrophages, ISACN considerably reduced the production of cytokines IL-1β, IL-6 and TNF-α. In the culture of macrophages stimulated with LPS, ISACN was effective in reducing the production of nitric oxide, the inflammatory cytokines IL-1β, IL-6 and TNF-α and the anti-inflammatory cytokine IL-10. To explore the mechanism of action of ISACN, experiments were performed with flow cytometry in which the expression of the CD69 molecules, toll-like receptor 4 (TLR4), inducible nitric oxide synthase (iNOS) and the active form of the protein kinases activated by mitogen ERK 1/2, JNK1/2 and p38, in addition to experiments with quantitative polymerase chain reaction where the gene expression of and iNOS in macrophages stimulated with LPS were determined. The treatment of macrophages with ISACN (10μM) reduced the expression of all analyzed molecules and reduced the gene expression of CD69 and iNOS. Considering the results obtained, we can suggest that ISACN had an anti-inflammatory effect and that this effect is associated with negative regulation of the TLR4/MAPK-ERK-JNK-p38 pathway.